1991
DOI: 10.1002/eji.1830210902
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid‐dependent and ‐independent mechanisms involved in lipopolysaccharide tolerance

Abstract: Injection of bacterial lipopolysaccharide (LPS) into animals results in a transient increase in serum tumor necrosis factor (TNF). Maximal increases in TNF were detected by 1 h and 3-4 h serum TNF was no longer apparent. These animals were LPS tolerant and a repetitive LPS stimulus did not result in an additional peak in TNF. Regulation of TNF expression in LPS-tolerant animals was at the transcriptional level as TNF mRNA was not apparent in spleen or peritoneal macrophages following a second LPS stimulus. Adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 43 publications
3
62
0
Order By: Relevance
“…The role of endogenous glucocorticoids in the regulation of LPS effects is supported by the fact that the high sensitivity of adrenalectomized animals to LPS shock can be reversed by administration of DEX [10]. Moreover, the progesterone and glucocorticoid inhibitor, RU-486, deactivates the state of tolerance to LPS [34], suggesting that the regulation of glucocorticoids and/or GcR is a key factor [10,28] in mechanisms where LPS is involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of endogenous glucocorticoids in the regulation of LPS effects is supported by the fact that the high sensitivity of adrenalectomized animals to LPS shock can be reversed by administration of DEX [10]. Moreover, the progesterone and glucocorticoid inhibitor, RU-486, deactivates the state of tolerance to LPS [34], suggesting that the regulation of glucocorticoids and/or GcR is a key factor [10,28] in mechanisms where LPS is involved.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the progesterone and glucocorticoid inhibitor, RU-486, deactivates the state of tolerance to LPS [34], suggesting that the regulation of glucocorticoids and/or GcR is a key factor [10,28] in mechanisms where LPS is involved.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In male mice, the occurrence of a tolerance in HPA axis response has been observed after chronic LPS or TNF-a but not after IL-1 administration. 191 The tolerance of the immune system for the release of TNF-a after multiple LPS injections seems to be mediated by the release of endogenous glucocorticoids as a consequence of the immune challenge, 189 thus indicating a negative feedback mechanism for glucocorticoids on the immune system. 142 Hadid et al showed that TNF-a plays an important role in stimulating the HPA axis after a single, but not after repeated, endotoxin injections and that an impairment in the HPA axis response to both immunoneuroendocrine (LPS) and neuro-endocrine (insulin) is present after repeated LPS administration.…”
Section: 161177178mentioning
confidence: 99%